2014
DOI: 10.1037/a0035340
|View full text |Cite
|
Sign up to set email alerts
|

A multisite examination of sexual violence risk and therapeutic change.

Abstract: The results are consistent with the dynamic nature of sexual violence risk and suggest that risk-relevant changes associated with participation in sexual offender treatment are linked to reductions in sexual offender recidivism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 42 publications
7
75
2
1
Order By: Relevance
“…However, it has been noted that anger is not necessarily a criminogenic need for all violent offenders, and particularly among those who demonstrate psychopathic traits (Howells, 2004). Even if anger is functionally related to violent behavior, it is also possible that other unmeasured indicators of risk (e.g., psychopathy) differentially impacted CSC change profiles, such that the extent of CSC in T-Ang and AX/O remained quite small (Olver, Nicholaichuk, Kingston, & Wong, 2014).…”
Section: Clinically Significant Changementioning
confidence: 98%
See 1 more Smart Citation
“…However, it has been noted that anger is not necessarily a criminogenic need for all violent offenders, and particularly among those who demonstrate psychopathic traits (Howells, 2004). Even if anger is functionally related to violent behavior, it is also possible that other unmeasured indicators of risk (e.g., psychopathy) differentially impacted CSC change profiles, such that the extent of CSC in T-Ang and AX/O remained quite small (Olver, Nicholaichuk, Kingston, & Wong, 2014).…”
Section: Clinically Significant Changementioning
confidence: 98%
“…Using the same change variables, a total of 10 Cox regression analyses were then performed. In these analyses, pre-treatment scores on each construct were controlled, as it has been argued that the amount to which an offender can change on a dynamic measure is restricted by his pre-treatment score (Olver et al, 2014). Nevertheless, the question of linking relevant treatment gains to reduced violent recidivism was not supported (Kroner & Yessine, 2013).…”
Section: Psychometric Change and Recidivismmentioning
confidence: 99%
“…In contrast, a number of studies with adult samples have found changes in risk total scores to predict reoffending (Beggs & Grace, 2011;Blanchard, 2013;Cohen, Lowenkamp, & VanBenschoten, 2016;de Vries Robbé et al, 2015;Hogan & Olver, 2016;Labrecque, Smith, Lovins, & Latessa, 2014;Lewis, Olver, & Wong, 2013;Michel et al, 2013;Olver, Christofferson, Grace, & Wong, 2014;Olver, Nicholaichuk, Kingston, & Wong, 2014;Olver et al, 2007;Raynor, 2007;Vose, Smith, & Cullen, 2013;Wilson, Desmarais, Nicholls, Hart, & Brink, 2013), particularly after other variables are controlled for in analyses (e.g., baseline scores; see Appendix 3,Supplemental Material). That said, a couple of studies have failed to find significant associations between change scores and reoffending (Hanson, Harris, Scott, & Helmus, 2007;Hanson, 2015;Goodman-Delahunty & O'Brien, 2014).…”
Section: Dynamic Change Hypothesis: Changes In Risk Will Predict Reofmentioning
confidence: 99%
“…This association did not reach significance in the full sample ( r = −.09) or for the low-risk group ( r = .01), but was significant for high-risk offenders ( r = −.15, p < .05). In other words, high-risk offenders who showed greater reductions in risk scores were less likely to reoffend (see also Olver, Nicholaichuk, Kingston, & Wong, 2014). For low-risk offenders, the level of improvement may not matter as much as it does for high-risk offenders because low-risk offenders are already relatively unlikely to reoffend.…”
Section: Changes In Risk Ratings and Reoffendingmentioning
confidence: 99%